(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
An anthropogenic activities leads to the presence of heavy metals in an environment which lead to environmental pollution. The area has become gradually engage with various waste such as animal waste, refused dump, spilling of petrol, kerosene, engine oil etc which can introduces the trace heavy metals. The research of background concentration of various heavy metals in soil samples taken from the NYSC orientation camp layout, which is situated in Katsina state, Nigeria, at latitudes of 643.7 m to 798.5 m and longitudes of 18 21I32IIE to 18 28I37II, was conducted. At intervals of 100 m, soil samples were taken from the locations, and each 100 m was divided into 10 m. (A1A10). In order to determine the concentration of the five examined heavy metals, a flame atomic absorption spectrophotometer (FAAS) was used (Co, Cr, Pb, Cd, Cu). The locations have an average heavy metal concentration of:- 0.16009, 0.55449, 0.02804, 0.00231, and 0.10406 ppm Respectively. Significant differences were observed by comparing the mean concentration of the heavy metals in the study areas with world health organization (W.H.O) threshold limit, national and international studies and it was suggested that the samples were not contaminated with the heavy metals. But the metals were detected and there is no need for immediate implementation and remediation measures by the relevant authority. It was and recommended that industries, factories and filling station should not be located at the area in order to minimize human activities so as to maintain stable environment free from pollutants